Extraction of polysaccharides from Amaranthus hybridus L. by hot water and analysis of their antioxidant activity - Tang, Yujia (PeerJ, 2019)
BACKGROUND: Amaranthus hybridus L. is an annual herb that belongs to the Amaranthceae family, a type of multi-purpose grain, vegetable and feed crop that has received considerable attention due to its great economic value. However, the composition of polysaccharides from A. hybridus has rarely been previously reported. METHODS: In this study, the aboveground part of A. hybridus was used as material and polysaccharides were isolated by the hot water extraction method. Two acidic polysaccharides were isolated and purified by the Sevage method and diethylaminoethyl cellulose-32 column chromatography. RESULTS: Two acidic polysaccharides were obtained from A. hybridus: AHP-H-1 and AHP-H-2. There were significant differences between the monosaccharide content from each sample according to gas chromatography-mass spectrometer. AHP-H-2 had higher antioxidant activity in vitro than AHP-H-1. The 2,2-diphenyl-1-picrylhydrazyl radical scavenging rate of two mg/mL AHP-H-2 was 80%, its hydroxyl radical scavenging rate was approximately 48.5%, its superoxide anion radical scavenging rate was 85.3% and its reduction ability of Fe(3+) was approximately 0.92. The total antioxidant capacity of each milligram of AHP-H-2 was 6.5, which was higher than ascorbic acid. CONCLUSION: The results of the study promote the effective use of A. hybridus and provide a theoretical basis for its development.